The Evidence for Prescription Information for Possible Use of a Repeated Dose of Oral Triptans: A Comment. Issue 5 (4th April 2016) - Tfelt‐Hansen, Peer; Jespersen, Stine F.
Abstract : A repeated dose of an oral triptan has been shown in randomized controlled trials (RCTs) to be ineffective as a treatment for no or partial response 2 hours after initial dosing but effective as treatment for headache recurrence. In the official prescription information in the United States, the United Kingdom, and Denmark repeated dosing of all seven oral triptans are recommended for headache recurrence but some triptans are also recommended for no or partial response, a use of a triptan deemed to be not beneficial in European and Canadian migraine guidelines. In summary, not all recommendations are based on evidence from RCTs. In addition, some recommendations are ambiguous and patients need clearer instructions. An example of such a clear British instruction in a patient leaflet instruction is presented at the end of the paper.